Literasi Hukum Tata Negara bagi Pemuda sebagai Upaya Pencegahan Konflik Sosio-Politik di Daerah - M. Harviend Gilang Perdana; Zesty Miranda; Kamal Fahmi Kurnia; Andriansyah Kartadinata (CV. Tripe Konsultan, 2026)
This community service activity aims to improve young people's understanding of constitutional law as a preventive measure against socio-political conflicts in the region. Low legal literacy and rampant political disinformation necessitate practical and participatory legal education. The activity was carried out in Korpri Jaya Village, Bandar Lampung City, involving 40 participants from among young people, youth organizations, and community leaders through workshops, focus group discussions, role-playing simulations, and the creation of educational digital media. The evaluation results showed a significant increase in participants' understanding of constitutional law principles and the formation of rational attitudes and respect for legal mechanisms. This activity also gave birth to the Korpri Jaya Law- Conscious Youth Forum as a platform for continuing legal literacy. Overall, this program emphasizes the importance of legal literacy as the foundation of local social and political resilience and a means of shaping a young generation with integrity, national insight, and a commitment to social peace.